THE METHODS OF TEACHING PHYSICS FOR UNDERGRADUATE STUDENTS AT OIL AND GAS INSTITUTE - Radis R. Kabirov; Alina Kh. Novikova; Nariman K. Dvoyashkin (Moscow Polytechnic University, 2016)
The article addresses various forms and methods of teaching physics for undergraduate students at technical faculties of O&G Institutes. These methods allows lectures to provide an optimal way for students to study physics in conditions of cutting down the time for learning this discipline. The authors discuss the modern teaching methods and technologies used in the educational process at the Physics Department of Almetyevsk State Oil Institute. The importance of interdisciplinary communication is noted. An efficiency of score-rating system in the current and final assessment of students' knowledge is shown.